TUTURAN EKSPRESIF SEBAGAI UNGKAPAN KESANTUNAN DAN KETIDAKSANTUNAN DALAM KUMPULAN DONGENG UNTUK ANAK - Tampubolon, Nesti Magdalena; Kushartanti, Kushartanti (UI Scholars Hub, 2025)
This research aims to describe expressive speech as an expression of politeness and impoliteness with moral values, which children learn during development. The data in this study used 42 expressive speeches of characters in the collection of fairy tales Jam Beker Raksasa & 9 Dongeng Seru Lainnya by Dian Kristiani. This research uses a qualitative approach through the analysis of Leech's politeness principle (1993), Leech's politeness scale (1993), Culpeper's impoliteness strategy (1996), and Linda and Eyre's moral values (1993). This research shows that expressive speech in this book uses more forms of impoliteness. Of the 42 expressive speeches, the researcher found 26 forms of impoliteness and 16 of politeness. In addition, the implications of using a form of politeness contain more moral values, respect, kindness, and friendliness, than impoliteness. Based on the data, the researcher found the strategy of direct impoliteness, violation of the approbation maxim, violation of the indirectness scale, fulfillment of the modesty maxim, fulfillment of the cost-benefit scale, and moral values of being.